2020
DOI: 10.1073/pnas.2001336117
|View full text |Cite
|
Sign up to set email alerts
|

Histamine provides an original vista on cardiorenal syndrome

Abstract: Cardiac and renal dysfunction frequently go hand in hand in hospitalized patients, and epidemiological studies have suggested an inverse correlation between renal function and cardiovascular morbidity and mortality. This relationship exists regardless of what organ is first affected (1). It reflects upon a complex interplay between heart and kidneys, with dysfunction of one organ often impairing the function of the other. The causal association between chronic kidney disease (CKD) and cardiovascular risk was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Previous reports have indicated that ANS mice are classified as type 3 or 4 CRS because renal damage precedes cardiac damage. 25 , 36 , 37 In this study, ANS mice was associated with cardiac fibrosis, cardiac dysfunction, overt albuminuria, and kidney interstitial fibrosis. ARNI treatment prevented the increase in cardiac fibrosis and inflammation in mice with ANS, whereas valsartan did not.…”
Section: Discussionmentioning
confidence: 63%
“…Previous reports have indicated that ANS mice are classified as type 3 or 4 CRS because renal damage precedes cardiac damage. 25 , 36 , 37 In this study, ANS mice was associated with cardiac fibrosis, cardiac dysfunction, overt albuminuria, and kidney interstitial fibrosis. ARNI treatment prevented the increase in cardiac fibrosis and inflammation in mice with ANS, whereas valsartan did not.…”
Section: Discussionmentioning
confidence: 63%
“…In the present study, we found that ANS mice exhibit structural abnormalities and impaired function of the kidneys prior to the decline in cardiac function. These suggested that ANS mice might be a model to elucidate the mechanisms for CRS causing transition from early to late-stage damages of cardiorenal tissues [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low activity of CASD is more likely to cause taurine deficiency which eventually leads to heart failure accompanied by myocardial fibrosis [41, 42]. Histamine, the product from histidine metabolism, is synthesized via catalytic decarboxylation of histidine by histidine decarboxylase (HDC) [43]. The HDC‐knockout (HDC −/− ) mice exhibited poorer left ventricular function and more adverse cardiac remodeling, in addition, histamine inhibited heart fibroblast proliferation in vitro, which suggested that histamine could modulate myocardial fibrosis to offer the cardioprotective effect [44].…”
Section: Discussionmentioning
confidence: 99%